Study and implementation of an image compression technique applied to medical images for archival and retrieval - Vasikaran, V. (2008)
The project called Study and Implementation of an image compression technique applied to medical images for archival and retrieval hereinafter shortly referred as MIARS (Medical image archival and retrieval system) was done as a partial fulfillment for my Master of Science. The main intention is to understand the image Archival and retrieval technology, and develop an application, which will meet the requirements of smaller scale medical establishments.